Advances in Curing Type 1 Diabetes: Stem Cell Therapy, Bioprinting, and Islet Transplantation - Bijaya Ghosh; Satarupa Acharjee; Akash Kr Samanta (Pharmaceutical and Biomedical Research, 2023)
Background and Objectives: Characterized by insulin insufficiency due to irreversible pancreas defects, type 1 diabetes is traditionally managed by regular insulin supplementation. Recently, tissue regenerative technology coupled with advanced-level surgical intervention has created hope for a cure. Research in this direction started with replacing defective pancreas with healthy ones. However, the strategy met showed limited success. Presently, extensive work is being conducted to replace the damaged β cells with healthy ones and create insulin-producing cells from stem cells. This study reviews various research strategies used to replace or regenerate β cells for curing diabetes. Methods: The literature survey was done on PubMed and Google Scholar until June 2023. The keywords used were “type 1 diabetes,” “cure,” “techniques,” “islet transplantation,” “encapsulation of β cells,” and “stem cells,” etc. Full-length research and review articles were used as the basis for the preparation of the manuscript. Papers describing the basic features and rationale supporting the development of technologies were included, whereas clinical aspects and case studies were excluded. Results: Mainly, three important approaches were discussed. Treatment involves transplantation of whole organ (pancreas), islet, and stem cells derived β progenitor cells. A brief discussion was included for each technique, such as the extraction of β cells and generation of insulin-producing cells from stem cells, along with the essential findings obtained from each approach. Conclusion: The review demonstrated various strategies researchers have undertaken to find a cure for type 1 diabetes in terms of insulin independence.